Analisis Timbulan dan Komposisi Sampah Domestik di Kecamatan Kesamben Kabupaten Jombang sebagai Dasar Perencanaan TPS 3R - Yayok Suryo Purnomo; Nanda Henik Pratiwi (Prosiding ESEC, 2022)
The lack of waste management facilities coupled with the amount of waste generation that continues to increase along with the increase in population causes the accumulation of waste at several points in Kesamben District. Most of the people throw their garbage on the side of the road, in the river, or by burning. For this reason, it is necessary to analyze the generation and composition of waste in Kesamben District so that a waste management system can be carried out in accordance with the rules. The research was conducted by measuring waste generation directly from 26 sampling points throughout the Kesamben District. The waste generation sampling procedure was carried out based on SNI 19-3964-1994. From the sampling activity that has been carried out, the resulting solid waste generation is 0.1393 kg/person/day. While the results of the analysis of the composition of the waste showed the types of organic waste, plastic, paper, cloth/textile, glass, Styrofoam, and diapers. With the percentage of waste composition, respectively, that is 64.55%; 19.7%; 8.49%; 1.71%; 0.41%; 0.75%; and 4.38%. From these results it can be concluded that the composition of household waste is dominated by organic waste. So that people should be able to take advantage of composting technology to manage waste in their homes and sort out plastic waste to reduce the amount of waste generated.